Minimum wages and unemployment - TEN, Gi Khan (KDI School, 2015)
The relationship between minimum wages and unemployment is a widely debated topic among economists and policy makers. However, only a few attempts to study this issue on Russian labor market have been done. By using one of the most effective empirical tools, which is Instrumental Variables approach, it was determined that minimum wages policies do have an adverse impact on unemployment rates in Russian regions. After exploiting an exogenous variation in minimum wages across regions and time, the results are expected to be unbiased and consistent. The results are robust to alternative model specifications.
Thesis(Master) --KDI School:Master of Development Policy,2015